PENGARUH WAKTU PENJEPITAN TALI PUSAT TERHADAP KADAR HEMOGLOBIN NEONATUS - Jomima Batlajery Batlajery; Yudhia Fratidhina Fratidhina; Hamidah Hamidah Hamidah (Poltekkes Kemenkes Jakarta III, 2014)
The timing of clamping talipusat in newborns can be a very important thing for the hemoglobin level that can influence the development of the next baby. This study aims to determine the effect of time of cord clamping on hemoglobin levels of infants aged 3 days. The research method used was a quasi-experiment. The sample was spontaneously born infants in accordance with the inclusion criteria, a total of 86 babies. Infant blood sampling performed by laboratory personnel Dinda Tangerang General Hospital on day 3. The results showed Hb baby is 14 to 20.8 g / dl and average 17.46 g / dl. Average Hb in cord clamping infants <2min was 15.9 g / dl. In cord clamping 2-7 minutes average Hb his 17.8 g / dl. Cord clamping> 7 minutes, the average infant Hb was 19.66 g / dl. There are differences in Hb levels among the three cord clamping time. The conclusion of this study is the length of time there is the influence of clamping the umbilical cord hemoglobin levels in infants aged 3 days. The longer the delay in clamping the umbilical cord, the baby will increase hemoglobin levels and reduce the risk of anemia in newborns. Suggestions for policy makers and health care to look back on the SOP of the delay cord clamp because of the research outputs can provide a significant effect on the increase in baby Hemoglobin and than preventing anemia.